Improved Structural Mapping and Conductive Targeting Delivered by a new 2.5D AEM Inversion Solver. Issue 1 (1st December 2016) - Paterson, Rod; Silic, Jovan; FitzGerald, Des
Abstract : The advantages of 2.5D (2D geology, 3D source) airborne electromagnetic inversion in 3D geological mapping applications and the identification of conductive drilling targets compared to the more commonly used CDI transforms or simple 1D inversions are demonstrated using examples from different geological settings. The 2.5D inversion application used in this work and described in Silic et al, 2015 is a substantially changed version of ArjunAir, Wilson et al., 2006, a product of CSIRO/AMIRA project P223F. The changes include a new forward model algorithm and a new inversion solver. The application enables the accurate simulation of 3D source excitation for full domain models inclusive of topography, non-conforming boundaries and very high resistivity contrasts. Solution is accurate for a geoelectrical cross-section which is relatively constant along a strike length that exceeds the AEM system footprint. The major innovation includes a new inversion solver with adaptive regularisation which allows the incorporation of a misfit to the reference model and the model smoothness function. The regularisation parameter is chosen automatically and changed adaptively at each iteration, as the model, the sensitivity and the roughness matrices are changing, Silic et al, 2015. Memory usage has been dramatically reduced and provides a usage estimate prior to execution. For speed the software has been parallelised using Intel MPI and can be used on standard computing hardware or computing clusters. Data from survey lines with lengths exceeding 30 kilometres can be inverted on high end laptop computers. The integrated software design allows the user to prepare a full survey inversion then execute this simply in a batch process. The user can visualise inversion progress at any time during process execution. We allow flexibility in the selection of components and in the estimation of noise. A non-specialist can obtain a high value result from our 2.5D AEM inversion in terms of it achieving a more realistic geological section. We show inversion examples from groundwater, minerals (VMS) and geological mapping AEM surveys projects and compare the results with known geology and drilling. We demonstrate the much improved mapping and target definition delivered by this inversion method when compared with the other more common transforms or inversion methods used on these projects.